Tinjauan Kesesuaian Pengelolaan Limbah Bahan Berbahaya dan Beracun Pada PT. X Kabupaten Bekasi - Zalfa Dziaul Hassalum; Venny Ulya Bunga (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
One company in the Bekasi Regency that specializes in handling toxic and hazardous waste is called PT X (B3). It is mandatory for all companies or activities that generate B3 waste to handle the waste in accordance with approved protocols. The Regulation of the Minister of Environment and Forestry (PERMENLHK) No. 6 of 2021, which addresses the storage, collection, transportation, and processing of B3 waste, is one of the laws governing the management of B3 waste. B3 waste collection and transportation are the operations of PT X. It's critical to recognize and assess current methods in hazardous waste management in order to guarantee compliance with relevant requirements. The aim of this research is to assess PT. X's degree of adherence to hazardous waste management standards. The evaluation and observation results demonstrate that PT. X didn't follow to all of the guidelines outlined in PERMENLHK No. 6 of 2021 and PERMENLH No. 14 of 2013, particularly with regard to the labeling and symbol installation on hazardous waste.